2004
DOI: 10.1038/sj.bjc.6601993
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial photodynamic therapy as salvage treatment for recurrent head and neck cancer

Abstract: Interstitial photodynamic therapy (IPDT) is a technique for applying photodynamic therapy (PDT) to internal tumours using light delivered via fibres inserted percutaneously. This phase I -II study assessed the safety and efficacy of IPDT for patients with persistent or recurrent head and neck cancer unsuitable for further treatment with surgery, radiotherapy or chemotherapy, recruited for 'last hope' salvage treatment. Patients were sensitised with 0.15 mg kg À1 mTHPC (meso-tetrahydroxyphenyl chlorin) 4 days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
123
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(132 citation statements)
references
References 20 publications
(18 reference statements)
1
123
0
5
Order By: Relevance
“…This observation needs to be followed up by animal studies to explore whether this phenomenon occurs in vivo before its potential for application in the clinical setting can be determined. Importantly, in the animal studies and human cases in which peripheral nerve sparing has been reported, the PDT was applied to the nerve trunk rather than to the ganglia containing the neuronal cell bodies (Ris et al, 1996;Kubler et al, 2003;Lou et al, 2004;Betz et al, 2007). Our in vitro study indicates that neurons might survive PDT directly applied to the ganglia if an appropriate mTHPC concentration and light dose were used, enabling PDT to be applied to areas of the body rich in neuronal cell bodies such as the DRGs without killing the neurons.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This observation needs to be followed up by animal studies to explore whether this phenomenon occurs in vivo before its potential for application in the clinical setting can be determined. Importantly, in the animal studies and human cases in which peripheral nerve sparing has been reported, the PDT was applied to the nerve trunk rather than to the ganglia containing the neuronal cell bodies (Ris et al, 1996;Kubler et al, 2003;Lou et al, 2004;Betz et al, 2007). Our in vitro study indicates that neurons might survive PDT directly applied to the ganglia if an appropriate mTHPC concentration and light dose were used, enabling PDT to be applied to areas of the body rich in neuronal cell bodies such as the DRGs without killing the neurons.…”
Section: Discussionmentioning
confidence: 96%
“…A range of photosensitisers have been developed, some of which have been used clinically for cancer treatment. One such photosensitiser (meta-tetrahydroxyphenyl chlorin (mTHPC) Foscan, Biolitec AG, Jena, Germany) has been reported to be effective in destroying tumour cells, although not causing major damage to the peripheral nerves in experimental models (Kubler et al, 2003) and in clinical practice (Ris et al, 1996;Lou et al, 2004;Betz et al, 2007). It is not yet clear whether this relative nerve sparing is a feature particular to mTHPC or shared with other photosensitisers.…”
mentioning
confidence: 99%
“…PDT may be able to provide palliation of the worst symptoms, such as bleeding, pain and airway obstruction without further loss of function, and if the volume of the active tumour is small, it may be able to stabilize the disease progression. For patients in whom all conventional options have failed, PDT is an approved indication using the photosensitizer mTHPC (Foscan) [20].…”
Section: (Ii) Head and Neckmentioning
confidence: 99%
“…For larger tumors, PDT can be given interstitially [75]. The response rates achieved are similar to those for other therapies, but PDT can also be used in patients who are unfit for further radiotherapy or surgery.…”
Section: Head and Neck Cancermentioning
confidence: 92%